The Silent Choke: A Fatal Case of Cafe Coronary Unveiled (Indian Journal of Forensic Medicine and Pathology, 2025)
Imagine someone enjoying a meal, perhaps a bit too much to drink, when suddenly they go silent, stand up, and then inexplicably collapse. This is the classic presentation of a cafe coronary, a condition where a piece of food completely obstructs the airway by lodging in the laryngopharynx and larynx. Unlike typical choking, there are often no dramatic struggles. The person might turn blue, cough violently for a moment, and then die relatively quietly. While it can be mistaken for a sudden heart attack, the true cause of death is generally attributedtoreÁexvagal inhibition of the heart, not a cardiac event. Autopsy often reveals a sizable, poorly masticated food bolus lodged in the larynx. A crucial detail is the absence of typical choking signs, which can be attributed to the deadening effect of high blood alcohol content on the gag reÁex.